FUNGSIONALISASI JABATAN PENGHULU DAN PENGARUHNYA TERHADAP KINERJAKUA KECAMATAN DI KOTA MANADO - Syarifuddin Syarifuddin (Institut Agama Islam Negeri (IAIN) Manado, 2018)
The existence of the chief as an official in the government has existed since the existence of the Islamic kingdom both on Java and outside Java, including in the Dutch colonial government. currently the head of the government based on the ministerial regulation on the utilization of state apparatus number 26 in 2005 has been determined as a functional position according to government regulation Number 16 of 1999 concerning functional positions of civil servants. The tasks of the headman in relation to the application of Islamic teachings and Shari'a in the field of marriage are not just a ceremonial event, but also as a means of manifesting the strictness of a Muslim and unifying the sacred bonds of inner and outer relations between a man and woman. therefore the tasks and roles of the peghulu are considered very important. This paper will discuss the functionalization of the position of the chief and its influence on the performance of the KUA. This study took a research study in KUA Sub-District throughout Manado. The results of the study were that the researchers found that KUA resources in Manado in general still had to be evaluated, because the staff were mostly women, the number of employees was still minimal and the educational background was mostly not S1. Whereas according to the rules, one KUA has 7 or 6 staff but in this city of Manado one KUA only has two or three staff. In addition to the implementation of KUA activities, the budget is still attached to the Department office so that all activities carried out are less effective. Keywords:Penghulu, KUA Manado, Functionalization, Islamic Shari'a. Keberadaan penghulu sebagai pejabat dalam pemerintahan telah ada sejak adanya kerajaan Islam baik di Jawa maupun luar Jawa termasuk pada pemerintahan kolonial Belanda. Saat ini penghulu berdasarkan peraturan menteri pendayagunaan aparatur negara nomor: 26 tahun 2005 telah ditetapkan sebagai jabatan fungsional sesuai peraturan pemerintah Nomor 16 Tahun 1999 tentang jabatan fungsional pegawai negeri sipil. Tugas-tugas penghulu berkaitan dengan penerapan ajaran dan syariat agama Islam dibidang pernikahan tidak sekedar sebuah acara seremonial, melainkan juga menjadi sarana perwujudan ketatan seorang muslim dan pemersatu ikatan suci lahir batin antara seorang pria dan wanita. Oleh karena itu tugas dan peran peghulu dirasa sangat penting. Tulisan ini akan membahas tentang fungsionalisasi jabatan penghulu dan pengaruhnya terhadap kinerja KUA. Penelitian ini mengambil studi penelitian di KUA Kecamatan se-kota Manado. Hasil dari penelitian adalah peneliti menemukan masalah bahwa sumberdaya KUA yang ada di kota Manado pada umumnya masih ada yang perlu dievaluasi, karena para stafnya kebanyakan perempuan, jumlah pegawainya masih minim dan latar belakang pendidikan kebanyakan bukan S1. Sedangkan menurut aturan yang ada satu KUA memiliki 7 atau 6 orang staf tetapi di kota Manado ini satu KUA hanya memiliki dua atau tiga orang staf. Selain itu untuk pelaksanaan kegiatan KUA, anggaran masihmelekat dengan kantor Departemen sehingga segala kegiatan yang dilakukan kurang efektif. Kata Kunci:Penghulu, KUA Manado, Fungsionalisasi, Syariat Islam.